Baby step in assembling and integrating the components of an artificial photosynthesis device with forced heterojunctions towards improved efficiency - Salgaonkar, Kranti N.; Bajpai, Himanshu; Mhamane, Nitin B.; Nalajala, Naresh; Chauhan, Inderjeet; Thakkar, Kavita; Joshi, Kavita; Gopinath, Chinnakonda S. (Journal of Materials Chemistry A, 2023)
How to achieve unassisted, economical, scalable, and sustainable artificial photosynthesis for liquid fuels/products with improved solar-to-fuel efficiency (STFE) to address a carbon-neutral economy remains a big question. To a large degree, the extent of charge separation at heterojunction interfaces and charge utilization determine the STFE. Towards this, BiVO3 is assembled from ionic-precursors into TiO2 pores, and integrated structurally and electronically with TiO2 on calcination as BiVO4 quantum dots (BVQDs). BVQDs in TiO2 (BVT) pores lead to an all-inorganic system with a sub-quadrillion number of heterojunctions in a 1 cm(2) device (contains similar to 25 mu g of BiVO4 (similar to 2.5 wt%) in the nanopores of similar to 975 mu g of TiO2 (similar to 97.5 wt%)) and facilitate artificial photosynthesis. We demonstrate 31-38% STFE with a photon to chemical conversion turn over frequency (ToF(P2C)) of 2.73 s(-1) with a 1 cm(2) wireless BiVO4-TiO2 artificial leaf (BVT-AL) device for HCHO and CH3OH. The sequential nature of CO2 reduction to HCHO and then to CH3OH is evident from the reaction results. (CO2)-C-13 isotopic labeling experiments confirm that the input CO2 is the source for product formation. A large increase in the photocurrent density and incident photon-to-current efficiency (IPCE) of BVT, over 100% for the BiVO4 photoanode in visible light, demonstrates and supports efficient visible light absorption, charge separation and migration to the redox sites. A device has been demonstrated to show sustainable activity in direct sunlight, and addresses scalability from 1 to 9 cm(2). Assuming no change (50% decrease) in the STFE, a 6.74 m(2) device is expected to convert 1 (0.5) kg h(-1) CO2 into C1-oxygenates in sunlight. DFT calculations carried out with anatase TiO2 (101) and BiVO4 (121) interfaces support many of the experimental findings, including electron flow from the latter to the former, and interaction of the oxygen of TiO2 with BiVO4 and vice versa at the interface towards forced heterojunctions.